Prognostic Indicator for Clinical Babesiosis in Cattle - Kumar, Bipin; Mondal, D.B.; Jithin , M.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Present Study has been carried out on the animals suffering from clinical bovine babesiosis in the Patna districts of Bihar, India. A total number of 36 lactating cows of different breeds and ages were included in the study to develop a prognostic indicator card for better and economic management of disease. There are two types of prognostic indicator systems that has been evolved viz numerical and categorical on the basis of oxidant marker, antioxidant status, trace mineral status, hematological changes and vital parameter changes between dead and survived suffering animals. Erythrocytic LPO in succumbed cases were significantly (P<0.01) higher than recovered ones. GPx, SOD and catalase in succumbed cases were significantly (P<0.01) lower than recovered ones. Trace elements Zn, Cu & Se in succumbed cases were significantly (P<0.01) lower than recovered ones. The body temperature, respiration and heart rate in dead cases were significantly (P<0.01) higher than recovered ones. In conclusion, Prognostic indicator card developed in the present study may be helpful in the management of clinical babesiosis in field condition .